Behavior of Following Health Protocols (Keeping Distance, Washing Hands and Wearing Masks) as a Form of State Defense in the Era of COVID-19 - Wijaya, Hanna; Wahyudi, Slamet Tri; Firmansyah, Yohanes (Cerdika: Jurnal Ilmiah Indonesia, 2021)
COVID-19 has become one of the problems that attacks all elements of national and state life. The effects of the COVID-19 Pandemic are not only related to health, but also attack the social aspects and resilience of a country. It is not surprising that the COVID-19 Pandemic can be classified as a non-military threat to a nation. This paper discusses the role of society through attitudes towards State defense such as Following Health Protocols (Keeping Distance, Washing Hands and Wearing Masks) as a Form of State Defense in the Era of COVID-19. This research is a literature review study that discusses social issues using 3 types of approaches, namely the statute approach, conceptual approach, and case approach. The results of this study reveal that we need to adjust to new behaviors in order to be healthier, safer, and more compliant. We need to use all tools available to motivate citizens. The role of the community in breaking the chain of transmission of the disease COVID-19 (risk of contracting and transmission) must be carried out by implementing a number of health protocols. The conclusion of this study is that COVID-19 has become a very big problem for all countries, forcing the security of the state. The main thing the community can do to combat a disease is with the Following Health Protocols such as Keeping Distance, Washing Hands and Wearing Masks.